Upaya Guru Mata Pelajaran Ekonomi Dalam Meningkatkan Aktivitas Belajar Siswa Pada Masa Pandemi Covid-19 di SMA Negeri 1 Takengon - Patin Nabilla; Ruaida Ruaida; Amiruddin Amiruddin (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2021)
During the Covid-19 pandemic, teachers are required to make different efforts and efforts than usual because every teaching and learning process activity is carried out remotely (online) and utilizes existing technology as a learning medium. Efforts taken by teachers in improving student learning activities through the use of Google Classroom and Google Meet. The purpose of this study is to find out what are the teacher's efforts in maximizing the use of the Google Classroom and Google Meet applications to increase student learning activities on economic subjects during the Covid-19 pandemic at SMA Negeri 1 Takengon, how student activities are in all learning activities. which has been designed both on Google Classroom and on Google Meet and what obstacles are faced by teachers when using Google Classroom and Google Meet during online learning. This study uses a qualitative approach with a descriptive type of research. The subjects of this study were 4 teachers of economics at SMA Negeri 1 Takengon. To answer the formulation of the problem, interviews were conducted. The results of interviews with 4 respondents found that the teacher's efforts in increasing learning activities using Google Classroom by uploading teaching materials such as modules, learning materials and LKPD in accordance with KD, also sharing youtube links and videos related to the material on the task features that will be discussed on Google Classroom. To improve student learning activities, teachers make discussions and monitor the course of discussions carried out on the available communication features and comment fields. The obstacles faced by teachers during online learning using Google Meet and Google Classroom services were that at first the teachers were not used to it and were still confused in using the features available in Google Classroom and Google Meet, Students lost motivation to learn during the online learning period during the Covid-19 pandemic. 19 and the limited facilities used for studying.Keywords: Effort, Google Classroom and Google Meet, Student learning activities.